Bringing forgiveness to life: Biographical preaching of Joseph’s forgiveness in the context of conflict and violence in northern Nigeri - Pele Daniel, Nicodemus (Stellenbosch Theological Journal, 2021)
Preaching forgiveness requires the use of stories, metaphors and images that are the product of creative imagination to shape the imagination of listeners. Preaching forgiveness without depiction tends to be abstract, and worst of all unconvincing. Therefore, the preacher has to find a way of picturing what he or she is talking about. This means preaching reconciliation involves the use of evocative images rather than conceptual structures. For example, making people change their attitudes toward a perceived enemy requires depiction. In addition, asking people to forgive in a situation of deep wounds created by divisions, conflicts and violence calls for the use of evocative images. What is more, telling warring parties, be they of different family, tribe, ethnic group, or religion, to come together, stay together and grow together in a situation of division, conflict and violence requires the use of pictures. Therefore, this article argues that biographical preaching is an effective way of preaching forgiveness because it entails picturing of biblical character so that people may see what is required of them to forgive and live a harmonious life with one another.